Strategi Mewujudkan Sekolah Kejuruan Berbasis Kewirausahaan dalam Peningkatan Kemandirian dan Kreatifitas Siswa Melalui Koperasi Sekolah - Armiati, Armiati (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT This article discusses the strategy for implementation of school based on entrepreneurship in enhancing student autonomy and creativity through school cooperation. The implementation of vocational school based on entrepreneurship requires some strategies. Firstly, we can do it with educational program and practice executed by vocational school and by the activity of school cooperation. Its final purpose is to make vocational school grade have the soul of entreprenueurship and also improve student autonomy and creativity so that they can learn how to compete in creating work field. Kata Kunci: Sekolah Kejuruan, kewirausahaan, kemandirian, kreativitas